Dreaming Possibilities: Reshaping Imaginaries with Feminism and Social Change - Liberti, Federica (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2023)
By using the feminist imaginary as a pedagogical tool for resistance and change, an experience of activism within the university context in Naples, Italy is explored. The article focuses on the potential transformative power of art as catalysis for deeper level emotional and spiritual learning transformation. The aim is trying to inspire critical conversations to rethink spaces and practices that allow community care, and conditions that include authenticity, resonance, reflection, and freedom. Engaging in the arts, aesthetics, and creative practices can contribute to a sense of hope, agency, and possibility with the potential to provide avenues for creative expression and innovation. Sharing narratives of possibility and engagement with the arts can promote community connections. This article highlights the way artistic practices contributed to the creation of a dynamic and inclusive creative landscape that challenges established norms while encouraging creative and critical thinking.